2006
DOI: 10.1158/1078-0432.ccr-06-0693
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-term Rofecoxib on Gastric Intestinal Metaplasia: Results of a Randomized Controlled Trial

Abstract: Purpose: Gastric cancer and its premalignant gastric lesion, intestinal metaplasia (IM), frequently express cyclooxygenase-2 (COX-2) at high levels. We tested whether long-term use of specific COX-2 inhibitors regress gastric IM. Experimental Design: This is a double-blind, randomized, placebo-controlled trial. Individuals with confirmed IM and Helicobacter pylori clearance were randomized to receive rofecoxib 25 mg daily or placebo. Endoscopy was done at baseline, at the end of year 1, and at the end of year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 26 publications
0
45
0
4
Order By: Relevance
“…Beyond the direct benefits and risks of eradication to the individual, the methods and consequences of attempted widespread eradication, such as increasing antibiotic resistance, must also be considered (Graham and Shiotani, 2008). A single trial has tested the effect of the NSAID rofecoxib on subjects with gastric pre-neoplastic lesions over 24 months and found no evidence of benefit, but this study was small and did not use cancer as an end point (Leung et al, 2006). The remarkably consistent observational results showing that NSAID use is associated with a reduced risk of gastric cancer may warrant a randomised trial in a suitable population at high risk for the disease in which side effects can be monitored closely.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the direct benefits and risks of eradication to the individual, the methods and consequences of attempted widespread eradication, such as increasing antibiotic resistance, must also be considered (Graham and Shiotani, 2008). A single trial has tested the effect of the NSAID rofecoxib on subjects with gastric pre-neoplastic lesions over 24 months and found no evidence of benefit, but this study was small and did not use cancer as an end point (Leung et al, 2006). The remarkably consistent observational results showing that NSAID use is associated with a reduced risk of gastric cancer may warrant a randomised trial in a suitable population at high risk for the disease in which side effects can be monitored closely.…”
Section: Discussionmentioning
confidence: 99%
“…Rofecoxib for 2 years in an RCT did not have a significant benefit in terms of intestinal metaplasia regression after H. pylori eradication [251]. Yanaoka et al reported a higher metachronous cancer incidence in patients treated with 300 mg/day of etodolac, after a mean follow-up period of 4.2 years.…”
Section: Surveillancementioning
confidence: 95%
“…The overall evidence regardless of type of drug used is inconsistent. Apart from one well-designed placebo-controlled RCT [251], the evidence suggesting a preventive effect of these chemopreventive agents on precancerous lesions outcome is drawn from lowquality studies, comprising one small RCT [252], one pilot study [253], and two prospective cohorts [254,255]. These were conducted in very heterogeneous populations (first-degree relatives of gastric cancer patients, dyspeptic patients with rheumatologic diseases, early gastric cancer patients, etc.)…”
Section: Surveillancementioning
confidence: 99%
“…Regular intake of Aspirin had to be maintained and the effect could not be confirmed for other NSAIDs as also reported in other studies [97,98]. Data on the benefits of COX-2 inhibitors is conflicting but show signs for improvement of pre-neoplastic conditions like chronic atrophic gastritis and gastric IM [99,100]. Comparison of these studies is often quite difficult due to hetergogeneous design, differing end-points and variation of inclusion and exclusion criteria.…”
Section: Chemopreventionmentioning
confidence: 93%